Does axitinib (AG-01376) have a future role in metastatic renal cell carcinoma and other malignancies?. Issue 10 (October 2010) - Goldstein, Robert; Pickering, Lisa; Larkin, James
Axitinib (Pfizer Inc., UK) is an oral small-molecule receptor tyrosine kinase inhibitor that targets angiogenesis. Axitinib has greater affinity and is a more selective inhibitor of VEGF receptor 1, -2 and -3, PDGFR and c-KIT than both sunitinib and sorafenib. It has encouraging efficacy and safety data in Phase II trials for metastatic renal cell carcinoma and advanced thyroid cancer patients. It is now being investigated in two Phase III trials in metastatic renal cell carcinoma and in Phase II trials in a range of tumor types. These trials will determine whether axitinib is an effective and safe antiangiogenic therapy.